2016
DOI: 10.1039/c5cy01943e
|View full text |Cite
|
Sign up to set email alerts
|

Novel AuCl3–thiourea catalyst with a low Au content and an excellent catalytic performance for acetylene hydrochlorination

Abstract: In this work, we synthesized a novel non-mercuric catalyst with HAuCl4·4H2O and thiourea as precursors, and active carbon (AC) as a support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 23 publications
(26 reference statements)
2
17
0
Order By: Relevance
“…Figure 6 represents the XRD spectra of Ag(I)MBT and Au(III)MBT complexes. The observed XRD spectra is in satisfactory agreement with the literature 5,1517 . In Fig.…”
Section: Resultssupporting
confidence: 90%
“…Figure 6 represents the XRD spectra of Ag(I)MBT and Au(III)MBT complexes. The observed XRD spectra is in satisfactory agreement with the literature 5,1517 . In Fig.…”
Section: Resultssupporting
confidence: 90%
“…Our TPR data clearly demonstrated that the onset reduction temperature for the Au 3+ species for the Au(H 2 O)/AC (OAR) catalyst was higher than for the Au(aq)/AC catalyst. The enhanced reduction temperature for the Au(H 2 O)/AC(OAR) catalyst can be attributed to the presence of sulfur atoms, which can prevent reduction of the cationic Au species [5,63]. The elemental mapping confirmed the presence of sulfur.…”
Section: The Valence and Reducibility Of Au Species Before And After supporting
confidence: 50%
“…Pioneering work by Hutchings revealed that gold in the ionic state possesses a unique catalytic activity on the hydrochlorination reaction of acetylene [4,5,6,7,8,9,10]. Thereafter, catalysts with high efficiency in the form of Au/carbon demonstrate that the gold is feasible as a substitute for the poisonous HgCl 2 catalyst [33,34,35,36,37,38,39,40]. Despite the impressive success achieved, the easy deactivation of Au 3+ catalyst originated from its high standard electrode potential [41,42] and sintering of the catalyst [12], which largely restrains its application in industry.…”
Section: Introductionmentioning
confidence: 99%